(untitled) (Contemporary Journal of Social Science Review, 2024)
Personality traits are significant factors influencing mental health outcomes, shaping how individuals perceive, cope with, and respond to stressors. In university students, understanding the role of personality can offer insights into individual differences in vulnerability or resilience to mental health challenges. The present study was conducted to find out the relationship among personality traits, ostracism, and mental health issues in university students. A correlational research design with a convenient sample technique was used to collect data (N=300; n=150 male and n=150 female) from the university students. Data was collected by utilizing three self-report measures i.e., a Substantively Valid Ostracism Scale (SVOS; Ferris, 2008), General Health Questionnaire (GHQ, Goldberg & Hillier, 1979), and Big Five Inventory (BFI, Goldberg, 1993). The results revealed that neuroticism, a personality trait, was positively correlated with ostracism and mental health issues, while openness to experience personality traits negatively correlated with ostracism and mental health issues in university students. Additionally, ostracism showed a significant positive correlation with mental health issues. Furthermore, females scored higher in ostracism and mental health issues compared to males. Gaining insight into these dynamics can help develop focused treatments and support systems that improve students’ general well-being in educational environments.